Asynchronous resonance in the driven Ising model on adaptive networks. Issue 5 (March 2020) - Zhu, Xiaolong; Mao, Zhipeng; Zhang, Haitian; Liu, Wanneng; Ni, Hang; Zheng, Guang; Zhan, Zhiming
Abstract: The stochastic resonance was investigated by the field-driven Ising model on adaptive networks. As the structure evolution probability η increases, it is found that the resonance undergoes three states: normal resonance, transition state and abnormal resonance. This work reveals significant effects of the coevolution of the topology and the dynamical processes, which even leads to counterintuitive phenomenon. When the coevolution of the topological structure and states of the system is not strong (corresponding to small η ) a weak external field will lead to a positive feedback. However, if the coevolution is strong enough (corresponding to large η ) the external field will cause a negative feedback.